Clinical case: Hepatoblastoma of the liver in the age not typical for hepatoblastoma - T.B. Tuyakova; V.S. Rakhmetova; G.A. Abai (LLC "MEDIAFORMAT", 2023)
Hepatoblastoma is a rare malignant tumor. One case of hepatoblastoma per 1 million of children under the age of 15 is diagnosed annually in the Republic of Kazakhstan (RK), which corresponds to 5-6 cases per year. In 90% of cases the tumor is diagnosed in children under the age of 5 and has two peaks of incidence: the first peak at birth or within the first month of life, and the second peak between the ages of 16 and 18 months. The cases involving patients older than 5 years are extremely rare. The paper reports the case of female patient, who was diagnosed with hepatoblastoma in the age not typical for malignant neoplasms of this type. The review of hepatoblastoma epidemiology, possible risk factors, clinical manifestations, diagnosis and treatment methods is provided in this issue.